2012
DOI: 10.1108/13287261211221146
|View full text |Cite
|
Sign up to set email alerts
|

Effects of e‐mail addiction and interruptions on employees

Abstract: Purpose -The purpose of this paper is to explore the effect of e-mail interruptions on tasks and to explore the concept of e-mail addiction within the workplace. Design/methodology/approach -Data were collected from a large car rental company in the UK. The first collection method involved observing the effects of simulated e-mail interruptions on seven employees by measuring the interrupt handling time, the interrupt recovery time, and the additional time required to complete the task given the number of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…Specifically on working age samples, excessive Internet use leads to information fatigue syndrome (i.e. information overload), high cognitive costs and emotional stress, chronic insomnia, relationship problems and burnout (Kakabadse et al, 2000;Marulanda-Carter and Jackson, 2012;Young, 2010). In short, the high presence of the Internet in our working and social lives and the negative consequences justify the need to understand the construct's prevalence and its drivers.…”
Section: The American Psychiatric Association Has Not Included Compmentioning
confidence: 99%
“…Specifically on working age samples, excessive Internet use leads to information fatigue syndrome (i.e. information overload), high cognitive costs and emotional stress, chronic insomnia, relationship problems and burnout (Kakabadse et al, 2000;Marulanda-Carter and Jackson, 2012;Young, 2010). In short, the high presence of the Internet in our working and social lives and the negative consequences justify the need to understand the construct's prevalence and its drivers.…”
Section: The American Psychiatric Association Has Not Included Compmentioning
confidence: 99%
“…Gutwin et al [20] supported this viewpoint and suggested that distributed developers do need to maintain awareness of one another by interviews and analyzing email messages in three successful OSS projects, i.e., NetBSD, Apache httpd, and Subversion. On the other hand, however, it is also argued that social communication have some negative effect on the efficiency of work-related activities [35], since both communication and working activities may compete for the time resources of individuals [36,56]. As a result, a large number of companies have begun monitoring the usage of emails or office telephones, and employees face consequences for misusing them [11].…”
Section: Related Workmentioning
confidence: 99%
“…Some well known authors like N. Carr (2011), S. Turkle (2011), J. Laniar (2011, have articulated the emerging discomfort felt by many of those regularly immersed in digital activities that they are losing their capacity to focus. The feeling of losing agency when engrossed in digital endeavours, and a dwindling sense of control on attention, is reported by many users (Zeldes et al 2007;Misra and Stokols 2012;Marulanda and Jackson 2012). Once again, most explanations of this phenomenon invoke the limits of human ability to cope with an overabundance of information and devices.…”
Section: Economy Of Attention: From Abundance To Scarcitymentioning
confidence: 99%